Konsep Maladministrasi Sebagai Pembaruan Model Pengungkapan Tindak Pidana Korupsi - Faisal, Muhammad; Rifai, Andi Tenri Famauri (Jurnal Suara Hukum, 2023)
This study aims to analyze the phenomenon of acts of corruption that have undergone changes in terms of form. The urgency of this research is to formulate several methods that can be more effective in following the development of acts of corruption that occur. This research is a normative legal research with a concept and statutory approach. The results of the study indicate that the model for disclosing criminal acts of corruption must be updated by looking at other aspects or forms of examination to open up initial loopholes in the disclosure of criminal acts of corruption. Maladministration examinations, which are currently still relatively new to be implemented, can be used as a model for disclosing criminal acts of corruption, especially those that ensnare state officials. A maladministration examination can reveal other hidden motives that influence a state official in fulfilling his administrative and legal obligations.